Exact Solutions to the Maxmin Problem max‖Ax‖ Subject to ‖Bx‖≤1 - Moreno-Pulido, Soledad; Garcia-Pacheco, Francisco Javier; Cobos-Sanchez, Clemente; Sanchez-Alzola, Alberto (Mathematics (Basel), 2020)
In this manuscript we provide an exact solution to the maxmin problem max ∥ A x ∥ subject to ∥ B x ∥ ≤ 1 , where A and B are real matrices. This problem comes from a remodeling of max ∥ A x ∥ subject to min ∥ B x ∥ , because the latter problem has no solution. Our mathematical method comes from the Abstract Operator Theory, whose strong machinery allows us to reduce the first problem to max ∥ C x ∥ subject to ∥ x ∥ ≤ 1 , which can be solved exactly by relying on supporting vectors. Finally, as appendices, we provide two applications of our solution: first, we construct a truly optimal minimum stored-energy Transcranian Magnetic Stimulation (TMS) coil, and second, we find an optimal geolocation involving statistical variables.